2006
DOI: 10.1207/s15516709cog0000_91
|View full text |Cite
|
Sign up to set email alerts
|

The Action–Sentence Compatibility Effect: It's All in the Timing

Abstract: When participants are asked to make sensibility judgments on sentences that describe action toward the body (i.e., "Mark dealt the cards to you") or away from the body (i.e., "You dealt the cards to Mark"), they are faster to respond when the response requires an arm movement in the same direction as the action described by the sentence. This congruence effect is known as the Action-Sentence Compatibility Effect (ACE). This study reports 4 experiments that extend our understanding of the ACE by exploring how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
133
4
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(165 citation statements)
references
References 22 publications
18
133
4
10
Order By: Relevance
“…But if readers perceptually simulate what is being described in the text (including the protagonist's movement) by activating their own motor and perceptual experiences, it is possible that their physical movement, if compatible with and tethered to the protagonist's described movement, can facilitate spatial updating in situation models. This possibility is in line with findings from studies demonstrating interactions between physical movement and the processing of described actions (e.g., Borreggine & Kaschak, 2006;Glenberg & Kaschak, 2002;Kaschak & Borreggine, 2008;Zwaan & Taylor, 2006) and overall with the idea that representations of spatial information in situation models are embodied (Zwaan, 2004).…”
supporting
confidence: 88%
“…But if readers perceptually simulate what is being described in the text (including the protagonist's movement) by activating their own motor and perceptual experiences, it is possible that their physical movement, if compatible with and tethered to the protagonist's described movement, can facilitate spatial updating in situation models. This possibility is in line with findings from studies demonstrating interactions between physical movement and the processing of described actions (e.g., Borreggine & Kaschak, 2006;Glenberg & Kaschak, 2002;Kaschak & Borreggine, 2008;Zwaan & Taylor, 2006) and overall with the idea that representations of spatial information in situation models are embodied (Zwaan, 2004).…”
supporting
confidence: 88%
“…For example, Glenberg and Kaschak (2002) showed that participants are faster to make an active response when the direction of motion described in a sentence matches the direction of motion required to make the response (see also Borreggine & Kaschak, 2006). Likewise, Zwaan and Taylor (2006) showed that sentences describing manual rotation (e.g., she turned the volume up/down) facilitate a congruent manual rotation of the hand (e.g., rotation of a knob to the right/left).…”
Section: Discussionmentioning
confidence: 98%
“…There is substantial experimental evidence for this view, suggesting that both motor simulation (Bergen & Wheeler, 2005, 2010Borreggine & Kaschak, 2006;Glenberg & Kaschak, 2002;Zwaan & Taylor, 2006) and perceptual simulation (Bergen et al, 2007;Kiefer, Sim, Herrnberger, Grothe, & Hoenig, 2008;Matlock, 2004;Richardson et al, 2003;Stanfield & Zwaan, 2001;Zwaan et al, 2002) are unconsciously and automatically engaged during language understanding. As was noted at the beginning of this article, evidence from brain imaging studies also shows that processing language associated with particular perceptual or motor functions activates the neural areas responsible for those same functions (Pulvermüller et al, 2001;Tettamanti et al, 2005).…”
Section: Discussionmentioning
confidence: 99%